Disabilitas dalam Teologi Katolik: Dari Liberalisme ke Politik Kasih - Hayon, Yohanes Wele (INKLUSI, 2019)
This article aims to re-question the relevance of Catholic political theology on the level of acceptance of people with disabilities. The author pointed out that the dominant ideology of liberalism, which separates the religious domain from politics, makes the discussion of disability limited to issues of equality. It missed the most sublime dimensions in the subject, namely recognition. So, how the political theology based on collective movement makes this lacking out? Referring to Jesus’ political action, the author argues that political involvement should presuppose a dimension of love that embraces all particulars. It should be based on agency strategy, without being trapped in claims of morality and binary opposition logic. Furthermore, the concept of disability is understood as a universal constitutive dimension that creates limitations as well as calls to be involved. This awareness is the basis for managing collective vulnerability as fellow sinful, unfixed, lacking, and not autonomous subjects. [Artikel ini bertujuan mempertanyakan kembali relevansi teologi politik agama Katolik dalam hal penerimaan terhadap kaum difabel. Di dalam artikel ini, penulis menunjukkan bahwa dominannya ideologi liberalisme yang memisahkan domain agama dari politik menyebabkan diskusi mengenai disabilitas dari perspektif teologi politik terkunci pada kesetaraan dan tidak memerhatikan dimensi paling sublim dalam diri subjek yakni pengakuan. Mengacu pada gerakan politik Yesus, penulis berargumen bahwa keterlibatan politik hendaknya mengandaikan dimensi kasih yang merangkul semua partikular tanpa terjebak pada klaim moralitas dan logika oposisi biner. Dengan menggunakan beberapa terma kunci dari para pemikir post-marxisme, post-strukturalisme dan psikoanalisis, konsep disabilitas dipahami sebagai dimensi konstitutif universal yang menciptakan keterbatasan sekaligus panggilan untuk terlibat. Kesadaran inilah yang menjadi landasan untuk mengelola kerentanan secara kolektif sebagai sesama subjek yang ‘berdosa’, ‘unfixed’, ‘lack’, dan tidak otonom.]